Ozone oxidation of wastewater containing trichlorobiphenyl and used transformer oil. Issue 9 (September 2020) - Abbasi, Umara; Bhatti, Zulfiqar Ahmad; Mahmood, Qaisar; Maqbool, Farhana; Faridullah,; Hayat, Malik Tahir
Abstract: Trichlorobiphenyl (TCB) is a persistent toxic organic compound and exerts more hydrophilicity than other polychlorinated biphenyl (PCB) compounds. PCBs have been used on large scale in transformer oil. To observe the strong ozone oxidation effect on the degradation of TCB in aqueous medium, synthetic wastewater was prepared from transformer oil with TCB. Microbubbles ozonation of TCB was done in order to completely oxidize it. A batch treatment system was used for 60 min in glass column with a diffuser at the bottom to convert ozone gas into microbubbles. GCMS analyzed TCB and other toxic compounds before and after the treatment. TCB was reduced to below detection limit during the first 20 min of ozonation. Ethylbenzene and 1-chloroheptacosine were identified after 10 and 20 min, the concentrations of these compounds increased to 1.45 and 3.9 mg/L after 60 min. Alkane with chlorine containing compounds were identified more than any other compounds. The alkanes compounds with chlorine, such as tetradecane 1-chloro, hexadecane 1-chloro, heptadecane 1-chloro, octadecane 1-chloro and nonadecane 1-chloro were found during 60 min of ozonation. Chemical oxygen demand (COD) in the wastewater reduced from 700 to 390 mg/L. Small increase in pH was observed from 7.7 to 8.3. In this study it was concluded that TCB and other pollutants in transformer oil were degraded with ozone dose, 0.05 g/min L in the shortest period of 60 min. Abstract : Environmental chemistry; Environmental engineering; Environmental hazard; Environmental pollution; Environmental toxicology; PCBs; Trichlorobiphenyl; Degradation; Ozonation; Diffuser; Oxidation and wastewater